Digital transformation in education: Implementation of augmented reality in learning media by teachers at SMKN 3 Yogyakarta - Jaedun, Amat; Hastutiningsih, Arum Dwi; Elviana, Elviana; Kholifah, Nur (Nur Science Institute, 2025)
This community service program addressed the limited digital literacy and pedagogical skills among vocational school teachers in developing interactive learning media. The program aimed to enhance teachers’ competence in creating Augmented Reality (AR)-based learning materials at SMKN 3 Yogyakarta. A workshop-based approach was implemented, involving direct training, guided practice, and mentoring in designing AR media using user-friendly platforms. Participants were introduced to the principles of AR, its application in education, and the technical steps for creating interactive content. Evaluation was conducted through pre- and post-training assessments, observations, and participant feedback. The results showed a significant improvement in teachers’ understanding and ability to integrate AR into their instructional design. Teachers demonstrated increased motivation to adopt innovative technology in the classroom and produced prototype AR media relevant to their teaching subjects. The program successfully fostered digital transformation in teaching practices by equipping educators with practical skills and confidence in utilizing emerging educational technologies.